Exchange rate pass-through in ASEAN : implications for the prospects of monetary integration in the region - Cortinhas, Carlos (2007)
This paper investigates, for the first time, the degree of exchange rate pass-through to domestic prices in all five founding members of ASEAN. For this purpose, a three variable recursive VAR model was applied which uses the Choleski decomposition method along the distribution chain of pricing, using data for the period 1968 to 2001. The results show that a strong case for entering a currency union can only be made for the cases of Singapore and Malaysia as in these countries there appears to be a case of exchange rate disconnect. A case for a common currency can also be made for Indonesia but for entirely different reasons. For this country, an independent monetary policy is a clear source of shocks to the economy and therefore a currency union would tend to eliminate then. A weaker case for a common currency can be made for the Philippines as evidence of some exchange rate pass-through to inflation was found but not to import prices. Finally, Thailand exhibits a clear case of exchange rate pass-through to import prices (but not to inflation) and thus evidence that a flexible exchange rate might be preferable as it provides the means to improve the country’s price competitiveness.